Usage of nutritional supplements for individuals with Down syndrome - Ergović Ravančić, Maja; Obradović, Valentina (Progress in Nutrition, 2021)
Down syndrome (DS), as one of the most common genetic disorders, is associated with numerous issues regarding physical and mental development. The introduction of nutritional supplementation in extremely high doses to the everyday routine of individuals with DS is one of the most controversial ideas proposed for the improvement of their physical and intellectual life. Although nutritional supplementation for DS was first proposed in 1940s, it gained popularity during the 1990s. Ever since, an enormous amount of research has become available on the Internet to support this claim, even explaining biochemical pathways relevant for the sustainability of the theory. At the same time, numerous papers which refute this theory and warn of the potential risks have been published, but many of them are not available for the wider population since access to scientific databases is often locked. Thus, parents and caregivers of individuals with DS are left without access to information relevant for their decision-making regarding the usage of supplementation. In this paper, a review of the newest research and conclusions regarding nutritional supplementation in DS is presented.